10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
Dysphagia is a common and clinically significant complication in idiopathic inflammatory myopathies (IIM), contributing to aspiration pneumonia, malnutrition, and reduced quality of life. However, its prognostic significance in terms of survival and swallowing outcomes remains unclear. A narrative review was conducted using PubMed to identify relevant studies published between January 2000 and April 2026. Dysphagia in IIM is associated with increased mortality, primarily due to aspiration-related complications and underlying disease severity. Emerging evidence indicates that this association may be modified by the presence of malignancy, particularly in dermatomyositis. Swallowing outcomes are heterogeneous: some patients show improvement with immunosuppressive therapy or intravenous immunoglobulin, whereas others experience persistent or progressive dysfunction, especially those with inclusion body myositis. Key prognostic factors include age, disease subtype, autoantibody status, and baseline severity of dysphagia. Dysphagia in IIM should be recognized as a clinically important manifestation associated with both survival and functional outcomes. Early identification and appropriate management are essential to improve patient prognosis. Further prospective studies are needed to establish standardized assessment and risk stratification strategies.